Modeling coastal inundation for adaptation to climate change at local scale: the case of Marche Region (central Italy) - Baldoni, Agnese; Melito, Lorenzo; Marini, Francesco; Galassi, Gaia; Giacomin, Patrizia; Filomena, Giorgio; Barbizzi, Natalino; Lorenzoni, Carlo; Brocchini, Maurizio (Frontiers in Climate, 2024)
Climate change is raising sea level rise and storminess effects on coastal systems, affecting the morphology of coastlines and impacting coastal communities and ecosystems.It is essential to gain information at an adequate scale to identify effective adaptation measures. This is of major importance in areas combining high vulnerability to climate change with high socioeconomic development, like the Northern Adriatic coastal area.To this aim, in this work two different approaches have been applied to investigate inland penetration of sea water along the Marche Region: a) a simple "bathtub" method applied to the entire Marche coastline, to highlight areas likely prone to intense inundation; b) a more accurate numerical model applied to two test sites, to gain detailed knowledge of inundation perimeters.Both approaches have been applied with forcing conditions provided by the Intergovernmental Panel on Climate Change and the Copernicus Climate Change Service through the RCP8.5 emission scenario projected to 2070.Information obtained with the model has been integrated in the Regional Plan for Adaptation to climate change to define specific adaptation measures.